A development of an accelerometer-based vibration detector system to evaluate hand motion in different shooting positions - Saputra, J.; Santoso, D. R.; Dharmawan, H. A.; Hasanah, R. N. (IEEE Xplore, 2022)
Shooting practice is wellknown to be correlated with shooting precision and accuracy. The rifle vibration and hand tremor influence the precision level itself. Identifying the level of movement as a function of hand tremors is necessary. In line with this, this research aimed to develop a vibration detector system based on an accelerometer for shooting practice. This development consisted of a microcontroller, accelerometer sensors, and a signal conditioning circuit. All sensors were placed in different positions related to the identified points: rifle muzzle, left hand, and right hand. A personal computer and a self-developed application were used to measure, record, and save all data into one file. The test was conducted by recording the hand tremor in three different positions: squatting, prone, and standing. The results show that the system works well in measuring the displacements. The first position (standing) has a movement of more than 0.1 m for all identified points at the first initial time. The squatting position is slightly different from the first stage, resulting in a movement of <0.10 m, <0.13 m, and <0.18 m, respectively, for the left-hand, right-hand, and muzzle points. The prone position has 0.14 - 0.21 m (left hand), -0.08 - 0.003 m (right hand), and 0.09 - 0.35 m (riffle muzzle) for all points. These values indicate that the developed system can be used as a device for shooting training. It can be concluded that the prone position has the most hand movement indicating the most vibration. The last movement is measured in the standing position, indicating the most stable position.